(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This particular paper clarifies the role of patriarchy and caste in contemporary Indian class society, as well as the organic connection which is present between class, caste, and patriarchy (as well as indirectly conventional Hindu religion). The present report tries to fill up the gap, to a small level, with reference to one of the non-Western societies, namely India. Power structures in Indian society are actually studied with the goal of understanding the connection between community qualities as well as power dispersion. The value of variables including community size, occupational variations, caste structure, organizational and educational innovations are examined.